Review: Public Health Nurses’ Roles and Competencies in Disaster Management - Putra, Ardia; Petpichetchian, Wongchan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2011)
Background: Currently, the incidence of disasters the biggest catastrophes that threaten people’s livelihoods, health, and even lives has been increasing around the world. This situation provides the challenge for health care professionals, particularly public health nurses (PHNs), to be actively involved in disaster management.Purpose: The purposes of this study are to review PHNs’ roles and competencies in disaster management in facing with natural disaster. Method: A relevant literature searched from databases: PubMed, CINAHL, the Cochrane and ProQuest Medical Library, and Science Direct were conducted. Key words used to retrieve included role and competency of PHNs or community nurses in disaster, disaster management, and disaster nursing. Searching was limited in English language, full text, and the year of publication starting from 2000. Results: Twenty-eight related studies were intensively reviewed. Several roles for PHNs in disaster management were identified. PHNs hold major roles in providing health management and assistance throughout the community and public healthcare system during all disaster phases including preparedness, response, and recovery phase. Moreover, determining PHNs’ involvement in disaster management requires certain competencies to assure their contribution in disaster events. In addition, training and education, and the experience with disaster event can influence the PHNs’ competency in responding to disaster occurrences. Conclusion: Literatures showed that PHNs play roles as one of the valuable resources and are actively involved in disaster management. PHNs’ roles and competencies in disaster management is necessary because they are well-recognized and trusted in the community and frequently work closely with the disadvantaged and vulnerable group who often affected by disasters.Key words: disaster management, public health nurses, roles, competency.